PENGARUH FRAMING EFFECT TERHADAP MINAT MENONTON GRAND FINAL PROGRAM INDONESIAN IDOL SPECIAL SEASON A NEW CHAPTER - Tuty Mutiah; titi widyaningsih; Ridzki Rinanto Sigit (Cakrawala - Jurnal Humaniora, 2022)
The pandemic Covid-19 has an effect on the media so that the framing effect is one way of making decisions by producers and their teams to continue to look for interesting television program presentation and creativity concepts. The framing effect aims to test whether the influence of program packaging, celebrities/guest stars, presenters and artistic arrangements on viewing interest (Case Study of Broadcasting Department Students at Taruna Bhakti Vocational High School Depok). The method uses which is then processed using SPSS. Framing theory proposed by Entman is the rationale for all research with the influence of the framing effect and Education-Entertainment (E-E) is a media study other than psychology on the interests, thoughts, attitudes, and behavior of individuals or viewers. The results of this study indicate that program packaging, celebrities, presenters and the artistic arrangement of the Indonesian idol program greatly affect viewing interest in terms of viewing interest indicators. Before the Indonesian idol program was broadcast, the audience looked for information on what songs to bring, who were the performers. When the Indonesian idol program was broadcast, the audience really liked the gimmick and performances of the performers. The audience also always watches, participates in voting and sends whatsapp to support Indonesian idol program participants. The author finds novelty in the research that the author takes by taking the framing theory, which is usually used for research on news programs and politics with agenda setting theory. Meanwhile, this study uses Framing theory with supporting anchovies for Entertainmente-Education (E-E) by selecting several aspects of reality in the Grand Final of the Indonesian Idol Special Season A New Chapter Program.Keyword : framing effect, Entertainmente-Education (E-E), interest in watching, Indonesian idol